Role and therapeutic potential of the NEDD4 family in breast cancer - Zhang, Xiaoxiao; Li, Sijie (Frontiers in Pharmacology, 2025)
The high incidence and mortality rates of breast cancer (BC) continue to pose a significant threat to patient survival and life expectancy. An increasing number of recent studies have demonstrated the crucial role of the ubiquitin-proteasome system (UPS) in cancer initiation and progression. Of particular significance is the aberrant expression of the NEDD4 family, which belongs to the HECT-type E3 ubiquitin ligases, in BC progression. This review synthesizes current knowledge about the interactions between the NEDD4 family and various tumor-related signaling pathways and their roles in BC biology, providing a theoretical foundation for exploring novel prognostic markers and treatment strategies.